Peningkatan Minat Belajar Peserta Didik Melalui Penerapan Model Project Based Learning Pada Pembelajaran Bahasa Inggris - S.DM, Arifudin; Korompot, Chairil Anwar; Riswan, Andi (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. This classroom action research (CAR) is titled 'Improving Students' Learning Interest through the Implementation of Project-Based Learning (PjBL) Model in English Language Teaching for Grade X.3 at SMA Negeri 9 Makassar.' The purpose of this CAR is to examine the improvement of students' learning interest in Grade X.3 at SMA Negeri 9 Makassar through the implementation of PjBL model. This research involves a sample of 36 students in Grade X.3 at SMA Negeri 9 Makassar, second semester of the academic year 2022/2023, consisting of 14 male students and 22 female students. Data collection was conducted through observation and questionnaire distribution. The research was carried out in three meetings, namely the initial observation, implementation of cycle I, and implementation of cycle II. Based on the observation results and questionnaire responses in the first meeting, the students showed a lack of interest in learning English. After implementing the PjBL model in cycle I, 27.4% of the students showed growing interest in learning, and in cycle II, approximately 99.8% showed increased learning interest, with a Sig. value (2-tailed) of 0.000 (0.000 < 0.05), indicating a significant difference in learning interest between the implementation of Action Cycle I and Action Cycle II. Based on the findings, it can be concluded that the implementation of PjBL is effectively improves students' learning interest in English at Grade X.3 at SMA Negeri 9 Makassar. This finding contributes significantly to strengthening our understanding of the effectiveness of PjBL in enhancing students' learning interest. This research also provides practical implications for educators in designing more engaging and interactive learning strategies to enhance students' learning interest in English. Thus, this research has a positive impact on the development of English language teaching at SMA Negeri 9 Makassar Keywords: Learning, Improvement, Interest, PjBL, Project